Optical-electrical synergy on electricity manipulating plasmon-driven photoelectrical catalysis. (June 2019) - Wang, Jingang; Mu, Xijiao; Sun, Mengtao
Graphical abstract: Abstract: In this review, we introduce electricity stimulating plasmon-driven photoelectrical synergic catalysis monitored by electrochemical surface-enhanced Raman scattering (EC-(SERS)) spectroscopy in liquid. Firstly, we introduce the principle and instrument of electricity stimulating plasmon-driven surface catalytic reactions. Secondly, we review recent experiments on electricity stimulating plasmon-driven photoelectron-catalytic reactions in liquid environments, including the plasmon-driven reduced catalysis reaction and the plasmon-driven oxidized catalysis reaction, respectively. The plasmon-driven reduced catalysis is priority to plasmon-driven reduced reactions in liquid. The influence of laser intensity, potential voltage, pH and local surface plasmon resonance factors on plasmon-driven catalysis reactions is analyzed in detail. Our review systemically provides advances in electrochemical plasmon-driven catalytic reactions in liquid.